Utilizing a Combined Approach to Assess the Antimicrobial Efficacy of Peracetic Acid on Chicken Thighs and Beef Trim - Billy Hughes; Cindy B Austin; Dana K Dittoe; Jessica Anne Brown; Kara B Mikkelson; Steven C Ricke (Meat and Muscle Biology)
Antimicrobial interventions are widely utilized in the meat and poultry industry as a way to reduce foodborne pathogens; however, little is known about their overall impact on the microbiota. The objective of this study was to evaluate the impact of peracetic acid (PAA), when used as a short-duration antimicrobial spray, on the pathogen load and microbiota of inoculated chicken thighs and beef trim. Thighs were inoculated with a cocktail of Salmonella spp. and Campylobacter jejuni and trim with a cocktail of Salmonella spp. and Shiga toxin-producing Escherichia coli (E. coli). Inoculated thighs and trim were either not treated (NT) or independently sprayed in a modified spray cabinet with one of the following treatments: 0, 200, 400, and 800 ppm PAA. Samples were rinsed and subsequently used for pathogen detection and microbiota analyses. Pathogens were enumerated by spread plating on selective media, and genomic DNA was extracted for 16S rRNA gene sequencing. Pathogen data were analyzed using ANOVA and linear regression, with means separated by Tukey’s Protected honestly significant differences (HSD; P≤0.05). Microbiota data were analyzed using the QIIME2 pipeline, with data considered significant at P≤0.05 for main effects and Q≤0.05 for pairwise differences. Results from this study demonstrate that a spray, with and without PAA, effectively lowered the level of pathogens compared to NT (P<0.05). Increasing PAA concentrations resulted in lower levels of Salmonella and Campylobacter on thighs (P<0.05, R2=0.44 and 0.55) and Salmonella and E. coli on trim (P<0.05, R2=0.18 and 0.17). The microbiota remained mostly unchanged, with pairwise differences being observed between 0 and 400 ppm and 0 and 800 ppm (P<0.05 Q<0.05) on the β-diversity metric Bray Curtis. The application of PAA as a short-duration antimicrobial spray is an effective intervention strategy to reduce pathogen load; however, efficacy may vary between meat product and target pathogen.